Ecosystem services provided by agroecosystems: A qualitative and quantitative assessment of this relationship in the Pampa region, Argentina - Ferraro, Diego Omar (2014)
The development of an analytical framework relating agricultural conditions and ecosystem services (ES) provision could be very useful for developing land-use systems which sustain natural resources for future use. According to this, a conceptual network was developed, based on literature review and expert knowledge, about the functional relationships between agricultural management and ES provision in the Pampa region (Argentina). We selected eight ES to develop this conceptual network: (1) carbon (C) balance, (2) nitrogen (N) balance, (3) groundwater contamination control, (4) soil water balance, (5) soil structural maintenance, (6) N2O emission control, (7) regulation of biotic adversities, and (8) biodiversity maintenance. This conceptual network revealed a high degree of interdependence among ES provided by Pampean agroecosystems, finding two trade-offs and two synergies among them. Then, we analyzed the conceptual network structure, and found that both environmental and management variables influenced ES provision. Finally, we selected four ES to parameterize and quantify along ten growing seasons (2000/2001 - 2009/2010) through a probabilistic methodology called Bayesian Networks. Only N balance was negatively impacted by agricultural management; while C balance, groundwater contamination control and N2O emission control were not. Outcomes of our work emphasize the idea that qualitative and quantitative methodologies should be implemented together to assess ES provision in Pampean agroecosystems, as well as in other agricultural systems.